Antimicrobial Sensitivity and Resistance Pattern in Surgical Site Infections following Gynaecological and Obstetrical Operations (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: Surgical Site Infections (SSIs) are one of the common problem in obstetrical and gynaecological operations. It is related to the increasing cost, morbidity and mortality. Objectives of this study were, find out the rate of surgical site infection, frequencies of various pathogens causing SSIs and their antibiotic sensitivity and resistance pattern in gynaecological and obstetrical operations in the Department of Obs & Gynae Chittagong Medical College, Chattogram.Materials and methods: This hospital based prospective longitudinal study was carried from January 2021 to July 2021 in the Department of Gynaecology and Obstetrics, Chittagong Medical College, Chattogram, Bangladesh. After operation, patients’ surgical wounds were inspected first on 5-7 th day and there after weekly up to 30 postoperative- day. If there had any features of wound infection, pus or discharge would have been collected from the wound. A total 100 pus or discharge were collected from the wound after obtaining written informed consent and according to the inclusion and exclusion criteria. Samples were processed following the standard laboratory technique.The isolates were identified by colony morphology, Gram’s staining and biochemical test according to standard laboratory test methods.Results: In this study most of the surgical site infections were caused by gram negative organisms (90%). Pseudomonas aeruginosa (36%) was the commonest organism responsible for SSIs. Staphylococcus species were responsible for SSIs in 6% of cases. In case of gram negative bacteria Amikacin and Imipenem were sensitive to about 89% and 91% microorganisms. While in case of gram positive organisms it were about 78% and 89%. Commonly used antibiotics in our set up included Ceftriaxone, Cefixime, Ciprofloxacin and Cefuroxime were sensitive in gram positiveorganisms 45%, 33%, 33% and 33% respectively. Butin case of gram negative organisms it were 76%, 63%, 79%, and 66%.Conclusion: Surgical site infections are the reflection of quality of hospital services. Once it was thought that the organisms responsible for the SSIs were derived from normal bacterial flora of the skin. But in last few years, it has been shown that the gram negative organisms are the main pathogens responsible for SSIs. Most of them are derived from the hospital environment.So the strict surgical ritual has come to mainstay in the management of the patients instead of being used antibiotics irrationally, which not only increases the chance of resistance to the micro-organisms but also glooming our future.JCMCTA 2021 ; 32 (2) : 115-121